OneMotoring: Driving the digital transformation of vehicle services in Singapore - KONG, Lily (Institutional Knowledge at Singapore Management University, 2022)
The OneMotoring portal is a one-stop gateway to vehicle-related services and an integral resource for the motoring community in Singapore. From real-time traffic updates to renewing road tax, paying transport-related fees, and supporting the entire lifecycle of vehicle ownership, the portal offers more than a hundred digital services delivered by the Land Transport Authority (LTA), the government agency overseeing land transport in the country. In the early 2000s, LTA was among the forerunners in the digitalisation of public services and had battled its fair share of challenges commonly encountered by agencies embarking on a digital transformation journey. Users’ lack of computer literacy, the loss of human touch in service delivery, the difficulty in authenticating user digital identity, and workforce transition were among the common pertinent issues. Through stakeholder engagement, work redesign, employee retraining, leveraging government-wide shared services, and active partnership with multiple entities, LTA had succeeded in surmounting those obstacles. While the portal continued to serve and meet most of the motorists’ needs, LTA did not rest on its laurels. Moving forward to 2022, LTA saw the opportunity to push the envelope further to serve motorists better. In the pipeline was a new round of system upgrades, which included the evaluation of newer technologies to speed up the delivery of services and policy changes. With so many digital possibilities presented by technological advancements, how best could LTA reimagine the delivery of vehicle services from the future of mobility perspective? This case introduces students to the digitalisation of public services in Singapore, specifically in the context of vehicle-related services for owners of private vehicles via the OneMotoring portal. Through a study of this case, students will be able to appreciate the importance of digitalisation in the delivery of public services. As they reflect on the challenges faced by the land transport agency in its digital transformation journey, they learn about strategies for overcoming these challenges and draw lessons from the agency’s experience on change management.